Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Kecamatan Teluk Betung Timur - Murtini; Mazwini, Vina; Husada, Hindiana Sava (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
To improve the quality and professional performance of East Teluk Betung District Office employees, one of the factors that can be applied in the work environment is organizational culture. Organizational culture can help employee performance because it creates an extraordinary level of motivation for employees at the East Teluk Betung sub-district office to try their best to take advantage of the opportunities offered by their organization. This research focuses on problem solving which aims to explain the relationship between one variable and another through qualitative and quantitative analysis. There is a significant influence between organizational culture (X) on employee performance (Y), with a regression model Y = 35.017 + 0.001X. From the results of the analysis by comparing the tcount and ttable values, it can be concluded that the organizational culture variable (X) tcount dangt; t table, or 1.839 andgt; 1.67, then H0 is rejected and H1 is accepted, which means organizational culture (X) has a significant effect on performance (Y). There is a significant influence between organizational culture (X) on employee performance (Y) with the regression model Y = 30.042 + 0.114X. The results of data processingobtained an Fcount value of 3.482 and an Fcount value of 3.482. greater than Ftable. Based on the results of the hypothesis test, it was decided to reject H0 and accept H1, which means that organizational culture (X) as a whole has a significant effect on employee performance (Y).